Battle deaths over time: What does the data say?. Issue 4 (29th July 2020) - Tarran, Brian
Abstract : Much ink has been spilled over the question of whether human deaths in battle have declined over time, and particularly since the end of World War II. But what does the data say? By Brian Tarran.